Safety and efficacy of the C-Tb skin test to diagnose Mycobacterium tuberculosis infection, compared with an interferon γ release assay and the tuberculin skin test: a phase 3, double-blind, randomised, controlled trial. Issue 4 (April 2017) - Ruhwald, Morten; Aggerbeck, Henrik; Gallardo, Rafael Vázquez; Hoff, Søren T; Villate, José I; Borregaard, Bettine; Martinez, José A; Kromann, Ingrid; Penas, Antón; Anibarro, Luis L; de Souza-Galvão, Maria Luiza; Sánchez, Francisca; et al.
Summary: Background: Targeted screening and treatment of Mycobacterium tuberculosis infection substantially reduces the risk of developing active tuberculosis. C-Tb (Statens Serum Institute, Copenhagen, Denmark) is a novel specific skin test based on ESAT-6 and CFP10 antigens. We investigated the safety and diagnostic potential of C-Tb compared with established tests in the contact-tracing setting. Methods: Negative controls, close contacts, occasional contacts, and patients with active pulmonary tuberculosis were enrolled at 13 centres in Spain. We compared C-Tb with the QuantiFERON-TB Gold In-Tube ([QFT] Qiagen, Hilden, Germany) interferon γ release assay (IGRA) and the purified protein derivative (PPD) RT 23 tuberculin skin test ([TST] Statens Serum Institute). All participants older than 5 years were tested with QFT. Some participants in the negative control group received C-Tb without the TST to test for potential interactions between C-Tb and PPD RT 23. The rest were randomly assigned in blocks of ten and tested with both C-Tb and TST, with five in each block receiving injection of C-Tb in the right arm and the TST in the left arm and five vice versa. The primary and safety analyses were done in all participants randomly assigned to a group who received any test. This trial is registered withClinicalTrials.gov, numberNCT01631266, and with EudraCT, number 2011-005617-36. Findings: From July 24, 2012, to Oct 2, 2014, 979 participants were enrolled, of whom 263 were negative controls, 299 were occasional contacts, 316 were close contacts, and 101 were patients with tuberculosis. 970 (99%) participants completed the trial. Induration sizes were similar for C-Tb and TST, but TST positivity was affected by BCG vaccination status. We found a strong positive trend towards C-Tb test positivity with increasing risk of infection, from 3% in negative controls to 16% in occasional contacts, to 43% in close contacts. C-Tb and QFT results were concordant in 785 (94%) of 834 participants aged 5 years and older, and results did not differ significantly between exposure groups. The safety profile of C-Tb was similar to that for the TST. Interpretation: C-Tb delivered IGRA-like results in a field-friendly format. Being unaffected by BCG vaccination status, the C-Tb skin test might provide more accurate treatment guidance in settings where the TST is commonly used. Funding: Statens Serum Institut.